2015
DOI: 10.3354/meps11426
|View full text |Cite
|
Sign up to set email alerts
|

Marine animal behaviour in a high CO2 ocean

Abstract: Recently, the effects of ocean acidification (OA) on marine animal behaviour have garnered considerable attention, as they can impact biological interactions and, in turn, eco system structure and functioning. We reviewed current published literature on OA and marine behaviour and synthesize current understanding of how a high CO 2 ocean may impact animal behaviour, elucidate critical unknowns, and provide suggestions for future research. Although studies have focused equally on vertebrates and invertebrates, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
115
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(131 citation statements)
references
References 112 publications
4
115
1
1
Order By: Relevance
“…Regardless, because submerged snails remain within the sea stars' preferred habitat and can likely be sensed more readily by them, such declines in the time of emergence could translate into an increased risk of predation. It also appears that periodic rebounds of pH to higher values lasting 18 h each day neither mitigate the initiation of behavioural impairment nor enable recovery of viable escape responses once the impairment has been established (see also [42]). To the extent that T. funebralis serves as a representative model for other intertidal gastropods that react to Pisaster as a generalist predator, these findings imply the potential for disruption of a substantial number of consumptive and non-consumptive links within the food web.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless, because submerged snails remain within the sea stars' preferred habitat and can likely be sensed more readily by them, such declines in the time of emergence could translate into an increased risk of predation. It also appears that periodic rebounds of pH to higher values lasting 18 h each day neither mitigate the initiation of behavioural impairment nor enable recovery of viable escape responses once the impairment has been established (see also [42]). To the extent that T. funebralis serves as a representative model for other intertidal gastropods that react to Pisaster as a generalist predator, these findings imply the potential for disruption of a substantial number of consumptive and non-consumptive links within the food web.…”
Section: Discussionmentioning
confidence: 99%
“…). This can result in an array of impacts to many marine organisms, including behavioural (Briffa, de la Haye & Munday ; Clements & Hunt ) and physiological (e.g. Pörtner ) effects.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that the early developmental stages of fishes are indeed vulnerable to elevated P CO2 including changes in metabolism and swimming duration (Pimentel et al, 2014a), swimming speed (Bignami et al, 2013), sensory perception and behavior (see reviews by Munday et al, 2012;Clements and Hunt, 2015), morphological deformations (Chambers et al, 2014;Pimentel et al, 2014b;Mu et al, 2015), and survival and growth (Kikkawa et al, 2003;Baumann et al, 2011;Frommel et al, 2011Frommel et al, , 2014. Other studies have shown that the early stages of fishes are relatively robust, remaining unaffected by elevated P CO2 (Hurst et al, 2012;Frommel et al, 2013), suggesting that sensitivity to OA is both species and life-stage specific.…”
Section: Introductionmentioning
confidence: 99%